Woman speaking at the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows a women speaking into a microphone with an African American woman, probably Jenifer Williams, standing off to the side. They are participants at the 1986 y-Walk. There is sound equipment in a chair next to the woman speaking.